Herpes simplex virus type-1 ocular infection in thrombospondin-1 deficient C57BL/6J mice - Aaron W. Kolb; Monica M. Sauter; Sarah Ferguson; Asha S. Jain; Nader K. Sheibani; Christine M. Sorenson; Curtis R. Brandt (PLoS ONE, 2026)
Herpes simplex virus type 1 (HSV-1) corneal infection triggers an immunopathological response and corneal neovascularization leading to vision impairment. Thrombospondin-1 (TSP-1) is a matricellular protein shown to regulate inflammatory processes and vascularization in the cornea. The purpose of this study was to determine if loss of TSP-1 alters the pathology of HSV-1 keratitis. The recombinant virus INV-2C or the low passage orolabial HSV-1 isolate, Ikey, were administered to scarified corneas of 8-week-old Thbs1 -/- and control C57BL/6J mice. Blepharitis, corneal neovascularization, corneal clouding, weight loss, viral titers, and mortality were determined on multiple days post infection. Corneal nerve loss was evaluated on day 2 and day 7. Neutralizing antibody, T-cell responses, and infiltrating cells in the aqueous and vitreous humors were quantified. There was no significant difference between Thbs1 -/- and C57BL/6J control mice when comparing any corneal disease outcome with either virus. Severe pan-uveitis developed in both C57BL/6J and Thbs1 -/- mice infected with the Ikey strain of virus. There were no significant differences in antibodies to HSV or in the number of HSV-1 specific IFN-g secreting T-cells in the spleen between C57BL/6 or TSP-1 -/- mice. The lack of TSP-1 did not affect the severity of corneal disease, immune responses to HSV-1, or sensory nerve loss suggesting either TSP-1 functions are not involved in HSV-1 pathogenesis or that other members of the TSP family can substitute for the loss of TSP-1.